Elements of Sri Lanka's Geopolitics: Impact on United States' Foreign Policy. (2nd January 2017) - Senaratne, Bhagya
ABSTRACT: This article examines whether the physical determinants of Sri Lanka have a significant impact on the formulation of the United States' foreign policy. It also analyses whether Sri Lanka's close proximity to the sea lines of communication (SLOCs) has any influence on the United States' urge to link businesses and people, and also to reaffirm its interests and influence in Sri Lanka. The paper will briefly touch upon the security and military advantages that the United States enjoys in South Asia. It also ascertains whether American foreign policy towards Sri Lanka will be largely driven by economic factors, and due to Sri Lanka's location as well as the ability to integrate the island nation to America's future interests in the region.